Layered heterostructure tungsten-copper composite material and preparation method thereof

The preparation of layered heterostructure tungsten copper composite materials through rapid sintering and alternating lamination methods has solved the problem of inversion of mechanical properties and conduction properties of existing tungsten copper composite materials, and achieved higher strength, conduction and wear resistance. At the same time, the preparation cost is reduced.

CN119502530APending Publication Date: 2025-02-25BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411673952.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

There is an inverted relationship between the mechanical properties and the conduction properties of the existing tungsten copper composite materials, and the preparation cost of layered tungsten copper composite materials is high, and the large thickness of the tungsten layer limits the improvement of its mechanical properties.

Method used

Rapid sintering technology is used to prepare high-density ultrafine or nanocrystalline tungsten copper composite materials, and then cut into thin sheets through wires and then stacked alternately to perform rapid sintering to form a layered heterostructure tungsten copper composite material.

Benefits of technology

The compression strength, conductivity and wear resistance of layered heterostructure tungsten copper composite materials are significantly improved, the preparation cost is reduced, and a more uniform oxide lubricating film is formed, which improves wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005146587900000011
    Figure HDA0005146587900000011
  • Figure HDA0005146587900000012
    Figure HDA0005146587900000012
  • Figure HDA0005146587900000021
    Figure HDA0005146587900000021
Patent Text Reader

Abstract

The invention discloses a layered heterostructure tungsten-copper composite material and a preparation method thereof, and belongs to the field of powder metallurgy. The tungsten-copper composite material with the layered heterostructure is formed by alternately distributing ultrafine / nano-structured high-tungsten-content tungsten-copper layers and ultrafine / nano-structured low-tungsten-content tungsten-copper layers or copper layers, and the tungsten-copper composite material with the layered heterostructure is formed by slicing an ultrafine / nano tungsten-copper composite material and then stacking and sintering the sliced ultrafine / nano tungsten-copper composite material. Compared with other tungsten-copper composite materials, the layered heterostructure tungsten-copper composite material provided by the invention has the advantages that due to the strengthening effect brought by the superfine / nano structure and the unique stress partition and current density partition in the bearing process brought by the uneven distribution of the tungsten phase; comprising a tungsten-copper layered tungsten-copper composite material formed by laminating and sintering a pure tungsten sheet and a pure copper sheet and a uniform-structure tungsten-copper composite material with the same components, and shows higher compressive strength, conductivity and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of powder metallurgy, and particularly relates to a layered heterogeneous structure tungsten-copper composite material with high comprehensive performance and a preparation method thereof. Background Art

[0002] Due to its good comprehensive properties such as high strength, high conductivity, wear resistance, and ablation resistance, tungsten-copper composite materials are widely used in the fields of electrical contacts, electrical machining electrodes, etc. Generally speaking, tungsten-copper composite materials are prepared by powder metallurgy and present a microstructure with uniform distribution of tungsten and copper. For tungsten-copper composite materials with this structure, the performance is affected by grain size and composition as follows: coarse-grained tungsten-copper composite materials have good conductivity, but low strength and wear resistance; ultrafine / nanostructured tungsten-copper composite materials have high strength and good wear resistance, but low conductivity; tungsten-copper composite materials can be strengthened by adding alloying elements or second phases, but their conductivity will also be reduced. Therefore, the mechanical properties and conductivity properties of tungsten-copper composite materials show an inverted relationship, which limits their service performance.

[0003] In addition, tungsten-copper composite materials can also be prepared by stacking and sintering tungsten foil and copper foil. For example, patents CN202111578364.4 and CN202210358124.1 respectively disclose methods for preparing layered tungsten-copper composite materials using pure tungsten foil as raw materials. According to relevant research (Sun et al., Composites Part B, 2024, 283: 111641), the strength, conductivity and wear resistance of layered tungsten-copper composite materials parallel to the direction of the layers are significantly improved compared with coarse-grained tungsten-copper composite materials with uniform structures. However, due to technical limitations, the thickness of tungsten foil is generally at the level of hundreds of microns, resulting in a relatively large thickness of the tungsten layer in the prepared layered tungsten-copper composite material, which limits the further improvement of its mechanical properties. At the same time, due to the high-density dislocations inside the tungsten foil and the interface problems between the tungsten-copper layers, the electrical conductivity of this layered tungsten-copper composite material is still somewhat lower than the theoretical value. Although the layered tungsten-copper composite material exhibits higher wear resistance, the larger layer thickness also prevents the layered tungsten-copper composite material from forming a stable and continuous oxide lubrication film on the surface during wear, so that its wear resistance still has a lot of room for improvement. Finally, the rolling process of tungsten foil is complicated, which increases the preparation cost of tungsten foil, resulting in a relatively high preparation cost of this layered tungsten-copper composite material. Summary of the invention

[0004] In view of the above problems, the present invention proposes a layered heterogeneous structure design scheme and a preparation method of a tungsten-copper composite material. The tungsten-copper composite material prepared by this method has significantly improved compressive strength, electrical conductivity and wear resistance compared with the existing uniform structure tungsten-copper composite material and layered tungsten-copper composite material.

[0005] The technical solution of the present invention is as follows:

[0006] A layered heterogeneous structure tungsten-copper composite material and a preparation method thereof, characterized by comprising the following steps:

[0007] (a) using rapid sintering technology to prepare a high-density tungsten-copper composite material with ultrafine grains or nanocrystalline structures and a high tungsten content (named A) and a tungsten-copper composite material with a low tungsten content or pure copper (named B);

[0008] (b) using wire cutting to cut the two tungsten-copper composite materials into thin sheets of the same size and specific thickness, respectively named A foil and B foil, B foil can also be directly made of copper foil, and the A foil and B foil are cleaned with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water in turn to remove the oxides on their surfaces;

[0009] (c) The A foil and the B foil are alternately stacked, placed in a mold, and rapidly sintered at a certain temperature and pressure to prepare the layered heterostructure tungsten-copper composite material of the present invention.

[0010] In the step (a), the grain size of the tungsten phase in the ultrafine crystal or nanocrystalline tungsten-copper composite material is 50-500 nanometers, the copper content of the tungsten-copper composite material corresponding to A is 10%-40% by mass, and the copper content of the tungsten-copper composite material corresponding to B is 60%-100% by mass.

[0011] In the step (b), the thickness of the tungsten-copper composite material sheet obtained by wire cutting is 50-500 microns. When B is pure copper foil, the thickness of the B foil is 10-500 microns.

[0012] In the step (c), the A foil and the B foil are alternately stacked, and the specific number of alternate stacking is adjusted as needed; the sintering temperature is 700-950 degrees Celsius, the pressure is 50-200 MPa, and the sintering time is 10-60 minutes. The prepared layered heterostructure tungsten-copper composite material exhibits a non-uniform layered structure in which tungsten-rich layers and tungsten-poor layers (or pure copper layers) are alternately distributed, and the grain size of the tungsten phase is between 50-500 nanometers.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. Compared with the layered tungsten-copper composite material prepared from tungsten foil as raw material, the layered heterogeneous structure tungsten-copper composite material prepared by the present invention replaces the tungsten layer with a tungsten-copper layer with an ultrafine / nanostructure. On the one hand, the preparation cost of the ultrafine / nanostructure tungsten-copper layer is lower than that of tungsten foil; in addition, the ultrafine / nanostructure tungsten-copper layer has the same or even higher strength as tungsten foil, as well as higher conductivity, which results in the layered heterogeneous structure tungsten-copper composite material prepared by the present invention having higher strength and conductivity than the layered tungsten-copper composite material prepared from tungsten foil as raw material.

[0015] 2. When subjected to wear, a more uniform and stable oxide lubricating film will be formed on the surface of the A layer (ultrafine / nano tungsten-copper layer) in the layered heterostructured tungsten-copper composite material prepared by the present invention, thereby reducing the friction coefficient of the tungsten-copper composite material. Finally, the layered heterostructured tungsten-copper composite material prepared by the present invention exhibits a lower wear rate than the layered tungsten-copper composite material prepared with tungsten foil as raw material.

[0016] 3. Compared with the traditional tungsten-copper composite material with uniform structure, the layered heterogeneous structure tungsten-copper composite material prepared by the present invention is actually a new type of tungsten-copper composite material with non-uniform distribution of tungsten phase. The non-uniform distribution of tungsten phase changes its stress distribution and electron transport path under load, so that the layered heterogeneous structure tungsten-copper composite material has higher strength, wear resistance and conductivity than the uniform structure tungsten-copper composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The SEM morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of the present invention;

[0018] Figure 2 A comparison chart of the compressive strength and electrical conductivity of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of the present invention and other tungsten-copper composite materials;

[0019] Figure 3 A comparison chart of the wear rate of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of the present invention and other tungsten-copper composite materials;

[0020] Figure 4 The SEM morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 2 of the present invention;

[0021] Figure 5 This is the SEM morphology of the (W-20Cu) / (W-90Cu) layered heterostructure tungsten-copper composite material prepared in Example 3 of the present invention.

[0022] Figure 2 and Figure 3In the figure, “heterogeneous layered tungsten copper” corresponds to the technical solution of the present invention; “layered tungsten copper prepared by tungsten foil” corresponds to a layered tungsten copper composite material prepared by sintering commercial tungsten foil and copper foil, the thickness of the tungsten foil and the thickness of the copper foil are 100 microns and 50 microns respectively, and have the same layered structure as Example 1; “coarse-grained tungsten copper” corresponds to a commercial W-20Cu composite material prepared by the melt infiltration method; “uniform nanostructured tungsten copper” corresponds to a nanostructured tungsten copper composite material with the same tungsten phase size and the same copper content as Example 1, and the tungsten phase is uniformly distributed. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments are only examples to assist in understanding the present invention and cannot be used as a basis for limiting the present invention.

[0024] Example 1

[0025] (a) Nano W-20Cu powder was prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material blocks with uniform nanocrystalline structure were prepared by rapid sintering technology (A);

[0026] (b) using wire cutting to cut the W-20Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, diameter 20 mm) with a thickness of 100 μm; and using wire cutting to cut a 50 μm thick pure copper sheet into a sheet with the same diameter as the A foil (B foil, diameter 20 mm), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in turn to remove oxides on their surfaces;

[0027] (c) The A foil and the B foil are alternately stacked (13 layers of A foil and 12 layers of B foil, which can be adjusted as needed), placed in a mold, and rapidly sintered at 900 degrees Celsius and 100 MPa for 20 minutes to prepare a (W-20Cu) / Cu layered heterostructure tungsten-copper composite material.

[0028] The scanning morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in this example is shown in FIG. Figure 1 As shown in Figure 2, its compressive strength is as high as 1200 MPa (according to GB / T 228.1, the pressure direction is parallel to the sheet direction), the electrical conductivity is 50% IACS (the test direction is parallel to the sheet direction), and the wear rate is 2.96×10 -6 mm 3 / (N·m) (the grinding material is silicon nitride ball, the pressure is 60N), which is 10%, 22% and 10% higher than that of layered tungsten-copper composite materials prepared by tungsten foil, and also significantly higher than that of coarse-grained tungsten-copper and uniform nanostructured tungsten-copper composite materials with the same composition. Figure 2 and Figure 3 shown.

[0029] Example 2

[0030] (a) Nano W-20Cu powder was prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material blocks with uniform nanocrystalline structure were prepared by rapid sintering technology (A);

[0031] (b) using wire cutting to cut the W-20Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, 20 mm in diameter), and using wire cutting to cut a 100-μm-thick pure copper sheet into the same diameter as the A foil (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in turn to remove oxides on their surfaces;

[0032] (c) The A foil and the B foil are alternately stacked (11 layers of A foil and 10 layers of B foil, which can be adjusted as needed), placed in a mold, and rapidly sintered at 900 degrees Celsius and 50 MPa for 10 minutes to prepare a (W-20Cu) / Cu layered heterogeneous structure tungsten-copper composite material. Its SEM morphology is shown in Figure 2. Figure 4 shown.

[0033] The test results show that its compressive strength is as high as 800MPa (according to GB / T 228.1, the pressure direction is parallel to the sheet direction), the conductivity is 47.6%IACS (the test direction is parallel to the sheet direction), and the wear rate is 3.1×10 -6 mm 3 / (N·m)(the grinding material is silicon nitride ball and the pressure is 60N).

[0034] Example 3

[0035] (a) Nano W-20Cu powder and nano W-90Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material blocks with uniform nanocrystalline structure (A) and W-90Cu composite material blocks with uniform nanocrystalline structure (B) were prepared by rapid sintering technology;

[0036] (b) using wire cutting to cut the W-20Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, 20 mm in diameter), and using wire cutting to cut the W-90Cu nanocomposite material (B) with uniform nanocrystalline structure into thin sheets (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in order to remove oxides on their surfaces;

[0037] (c) The A foil and the B foil are alternately stacked (12 layers of A foil and 11 layers of B foil, which can be adjusted as needed), placed in a mold, and rapidly sintered at 900 degrees Celsius and 100 MPa for 10 minutes to prepare a (W-20Cu) / (W-90Cu) layered heterogeneous structure tungsten-copper composite material. Its SEM morphology is shown in Figure 2. Figure 5 shown.

[0038] The test results show that its compressive strength is as high as 1380MPa (according to GB / T 228.1, the pressure direction is parallel to the sheet direction), the conductivity is 55.1%IACS (the test direction is parallel to the sheet direction), and the wear rate is 4.1×10 -6 mm 3 / (N·m)(the grinding material is silicon nitride ball and the pressure is 60N).

[0039] Example 4

[0040] (a) Nano W-30Cu powder and nano W-90Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-30Cu composite material blocks with uniform nanocrystalline structure (A) and W-90Cu composite material blocks with uniform nanocrystalline structure (B) were prepared by rapid sintering technology;

[0041] (b) using wire cutting to cut the W-30Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, 20 mm in diameter), and using wire cutting to cut the W-90Cu nanocomposite material (B) with uniform nanocrystalline structure into thin sheets (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in order to remove oxides on their surfaces;

[0042] (c) The A foil and the B foil are alternately stacked (8 layers of A foil and 7 layers of B foil, which can be adjusted according to needs), placed in a mold, and rapidly sintered at 800 degrees Celsius and 100 MPa for 60 minutes to prepare a (W-30Cu) / (W-90Cu) layered heterostructure tungsten-copper composite material.

[0043] Example 5

[0044] (a) Nano W-40Cu powder and nano W-70Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-40Cu composite material blocks with uniform nanocrystalline structure (A) and W-70Cu composite material blocks with uniform nanocrystalline structure (B) were prepared by rapid sintering technology;

[0045] (b) using wire cutting to cut the W-40Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, 20 mm in diameter), and using wire cutting to cut the W-70Cu composite material (B) with uniform nanocrystalline structure into thin sheets (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in order to remove oxides on their surfaces;

[0046] (c) The A foil and the B foil are alternately stacked (15 layers of A foil and 14 layers of B foil, and the specific number can be adjusted as needed), placed in a mold, and rapidly sintered at 800 degrees Celsius and 50 MPa for 40 minutes to prepare a (W-40Cu) / (W-70Cu) layered heterostructure tungsten-copper composite material.

[0047] Example 6

[0048] (a) Nano W-30Cu powder and nano W-80Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-30Cu composite material blocks with uniform nanocrystalline structure (A) and W-80Cu composite material blocks with uniform nanocrystalline structure (B) were prepared by rapid sintering technology;

[0049] (b) using wire cutting to cut the W-30Cu composite material (A) with uniform nanocrystalline structure into 300 μm thick sheets (A foil, 20 mm in diameter), and using wire cutting to cut the W-80Cu composite material (B) with uniform nanocrystalline structure into 300 μm thick sheets (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in order to remove oxides on their surfaces;

[0050] (c) The A foil and the B foil are alternately stacked (6 layers of A foil and 5 layers of B foil, and the specific number can be adjusted as needed), placed in a mold, and rapidly sintered at 900 degrees Celsius and 150 MPa for 20 minutes to prepare a (W-30Cu) / (W-80Cu) layered heterostructure tungsten-copper composite material.

[0051] Example 7

[0052] (a) Nano W-10Cu powder was prepared by freeze-drying hydrogen reduction technology, and then a W-10Cu composite material block with uniform nanocrystalline structure was prepared by rapid sintering technology (A);

[0053] (b) using wire cutting to cut the W-10Cu composite material (A) with uniform nanocrystalline structure into thin sheets (A foil, 20 mm in diameter), and using wire cutting to cut a 200-μm-thick pure copper sheet into sheets with the same diameter (B foil, 20 mm in diameter), and then using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean the A foil and B foil obtained by wire cutting in turn to remove oxides on their surfaces;

[0054] (c) The A foil and the B foil are alternately stacked (5 layers of A foil and 4 layers of B foil, which can be adjusted according to needs), placed in a mold, and rapidly sintered at 900 degrees Celsius and 100 MPa for 20 minutes to prepare a (W-10Cu) / Cu layered heterostructure tungsten-copper composite material.

Claims

1. A method for preparing a layered heterostructured tungsten-copper composite material, characterized in that: The following steps are involved: (a) using rapid sintering technology to prepare a high-density tungsten-copper composite material with a high tungsten content and an ultrafine grain or nanocrystalline structure (named A) and a tungsten-copper composite material with a low tungsten content or pure copper (named B); (b) using wire cutting to cut the two tungsten-copper composite materials into thin sheets of the same size and specific thickness, respectively named A foil and B foil, B foil or directly using copper foil, and using sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to clean A foil and B foil in turn to remove oxides on their surfaces; (c) The A foil and the B foil are alternately stacked, placed in a mold, and rapidly sintered at a certain temperature and pressure to prepare the layered heterogeneous structure tungsten-copper composite material of the present invention.

2. The method for preparing a layered heterostructured tungsten-copper composite material according to claim 1, characterized in that: In the step (a), the grain size of the tungsten phase in the ultrafine crystal or nanocrystalline tungsten-copper composite material is 50-500 nanometers, the copper content of the tungsten-copper composite material corresponding to A is 10%-40% by mass, and the copper content of the tungsten-copper composite material corresponding to B is 60%-100% by mass.

3. The method for preparing a layered heterostructured tungsten-copper composite material according to claim 1, characterized in that: In the step (b), the thickness of the tungsten-copper composite material sheet obtained by wire cutting is 50-500 microns. When B is pure copper foil, the thickness of the B foil is 10-500 microns.

4. The method for preparing a layered heterostructured tungsten-copper composite material according to claim 1, characterized in that: In the step (c), the A foil and the B foil are stacked alternately, and the specific number of alternate stacking is determined according to needs.

5. The method for preparing a layered heterostructured tungsten-copper composite material according to claim 1, characterized in that: In the step (c), the sintering temperature is 700-950 degrees Celsius, the pressure is 50-200 MPa, and the sintering time is 10-60 minutes. The prepared layered heterostructure tungsten-copper composite material exhibits a non-uniform layered structure in which tungsten-rich layers and tungsten-poor layers are alternately distributed, and the grain size of the tungsten phase is between 50-500 nanometers.

6. A layered heterogeneous structure tungsten-copper composite material prepared according to the method of claim 1, having a non-uniform layered structure in which tungsten-rich layers and tungsten-poor layers are alternately distributed.

Citation Information

Patent Citations

  • Preparation method of tungsten / copper layered composite material for thermonuclear fusion

    CN114701237A

  • Low-temperature rapid preparing method for high-density nanocrystalline tungsten copper base block composite materials

    CN109852861A

  • High-strength and high-conductivity ultra-fine grain tungsten-copper composite material and preparation method

    CN114086013A

  • Tungsten / copper layered composite material, preparation method and application thereof

    CN114193856A

  • Preparation method of tungsten-copper composite material

    CN117500247A